Vitamin D3 supplementation does not improve sprint performance in professional rugby players: A randomized, placebo-controlled, double-blind intervention study - Fairbairn, K. A.; Ceelen, I. j. M.; Skeaff, C. M.; Cameron, C. M.; Perry, T. L. (International Journal of Sport Nutrition and Exercise Metabolism, 2018)
Vitamin D insufficiency is common in athletes and may lower physical performance. Many cross-sectional studies associate vitamin D status with physical performance in athletes; however, there have been few prospective randomized controlled trials with adequate statistical power to test this relationship, and none in the southern hemisphere. Thus, a prospective double-blind, randomized, placebo-controlled intervention trial was conducted involving 57 professional rugby union players in New Zealand. Participants were randomized to receive 50,000 IU of cholecalciferol (equivalent to 3,570 IU/day) or placebo once every two weeks over 11-12 weeks. Serum 25(OH)D concentrations and physical performance were measured at baseline, weeks 5-6, and weeks 11-12. Mean (SD) serum 25(OH)D concentrations for all participants at baseline was 94 (18) nmol/L, with all players above 50 nmol/L. Vitamin D supplementation significantly increased serum 25(OH)D concentrations compared to placebo, with a 32 nmol/L difference between groups at 11-12 weeks (95% CI, 26-38; p < 0.001). Performance in five of the six tests at study completion, including the primary outcome variable of 30-m sprint time, did not differ between the vitamin D supplemented and placebo groups (p > 0.05). Performance on the weighted reverse-grip chin up was significantly higher in players receiving vitamin D compared with placebo, by 5.5 kg (95% CI, 2.0-8.9; p = 0.002). Despite significantly improving vitamin D status in these professional rugby union players, vitamin D supplementation had little impact on physical performance outcomes. Thus, it is unlikely that vitamin D supplementation is an ergogenic aid in this group of athletes.